The advantages and disadvantages of cast iron cookware: A comprehensive review - Xaminov Burkhon Turgunovich; Abdunazarov Shoxzodbek Utkirjon ugli; Rabbimov Elmurod Farhod ugli; Bakhriddinova Dilnora Sharifjon kizi (Global Scientific Publishing, 2023)
Cast iron cookware has been in use for centuries, but its popularity waxes and wanes with time. This review aims to provide a comprehensive analysis of the advantages and disadvantages of cast iron cookware based on empirical evidence. The study found that cast iron cookware is durable, versatile, and retains heat well. However, it also has some drawbacks, such as its weight, difficulty in cleaning, and the tendency to rust. The study concludes that while cast iron cookware has its limitations, it can be an excellent investment in the kitchen for those willing to put in the extra effort to maintain it properly.
Keywords: Cast iron cookware; advantages; disadvantages